Meningkatkan motivasi membaca - Muhammad Hamzah A.Sofyan (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2015)
Libraries have a very important role in fostering interest in reading among the public. This role can contribute to library to promote the library, so that society interested in coming to the library. Reading is a powerful source of motivation for someone to recognize and remember and evaluate the texts have been read, which is an exciting learning experience and will affect the shape and intensity of a person in determining its goals later in the future.